POSTPRANDIAL TRIGLYCERIDE AND TESTOSTERONE IN WOMEN WITH CARDIOVASCULAR DISEASES (Iraqi Journal of Medical Sciences, 2016)
Background:High androgen levels may increase cardiovascular disease (CVD) risk in women through adverse effects on lipids, blood pressure, and glucose metabolism. Lipid abnormalitiesare often found in women with CVD.Objective:To study the relationship between postprandial triglycerides (TG) as a risk factor for cardiac disease and the androgenic activity in postmenopausal women with CVD.Methods: Postprandial lipid profile and sex hormone levels were measured in 30 patients with CVD and 25 postmenopausal women age and body mass Index (BMI) matched served as control group.Testosterone and sex hormone binding globulin (SHBG), Estradiol (E2), follicular stimulating hormone (FSH) and luteinizing hormone (LH) were estimated.Results:Postprandial TG, high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and atherogenic index (AI) were different between the two groups (P?0.001). The SHBG and Free Androgenic Index (FAI) were significantly higher in the CVD postmenopausal women (P? 0.001) while no differences in testosterone, LH, FSH, and E2 levels noticed between CVD patients and the control group. Serum testosterone levels correlated positively with the postprandial TG and the atherogenic index, and negatively with HDL-C in the CVD patients.Conclusion:Elevation in androgenic activity could be a cause of higher elevation in postprandial serum TG which may increase the risk of CVD in women.Key Words:postmenopausal women, cardiovascular disease, postprandial lipid profile, testosterone, sex hormone binding globulin, free androgenic index
Keywords: postmenopausal women; cardiovascular disease; postprandial lipid profile; testosterone; sex hormone binding globulin; free androgenic index